Getting to Work : Unlocking Women's Potential in Sri Lanka's Labor Force - Solotaroff, Jennifer L.; Joseph, George; Kuriakose, Anne; Sethi, Jayati (Washington, DC: World Bank, 2017)
Sri Lanka has shown remarkable persistence in low female labor force participation rates—at 36 percent in the past two years, compared with 75 percent for same-aged men—despite overall economic growth and poverty reduction over the past decade. The trend stands in contrast to the country’s achievements in human capital development that favor women, such as high levels of female education and low total fertility rates, as well as its status as a lower-middle-income country. This study intends to better understand the puzzle of women’s poor labor market outcomes in Sri Lanka. Using nationally representative secondary survey data—as well as primary qualitative and quantitative research—it tests three hypotheses that would explain gender gaps in labor market outcomes: (1) household roles and responsibilities, which fall disproportionately on women, and the associated sociophysical constraints on women’s mobility; (2) a human capital mismatch, whereby women are not acquiring the proper skills demanded by job markets; and (3) gender discrimination in job search, hiring, and promotion processes. Further, the analysis provides a comparison of women’s experience of the labor market between the years leading up to the end of Sri Lanka’s civil war (2006–09) and the years following the civil war (2010–15). The study recommends priority areas for addressing the multiple supply- and demand-side factors to improve women’s labor force participation rates and reduce other gender gaps in labor market outcomes. It also offers specific recommendations for improving women’s participation in the five private sector industries covered by the primary research: commercial agriculture, garments, tourism, information and communications technology, and tea estate work. The findings are intended to influence policy makers, educators, and employment program practitioners with a stake in helping Sri Lanka achieve its vision of inclusive and sustainable job creation and economic growth. The study also aims to contribute to the work of research institutions and civil society in identifying the most effective means of engaging more women—and their untapped potential for labor, innovation, and productivity—in Sri Lanka’s future.